Grey Road Sections on Main Roads in Rural Areas: - Development, application and assessment of a Category Based Identification Method - Sørensen, Michael (Proceedings from the Annual Transport Conference at Aalborg University, 2006)
This paper is based on the PhD-thesis: ”Hazardous road sections in rural areas – develop- ment, application and assessment of severity based methods for identification, analysis and improvement of hazardous road sections” (Sørensen 2006) (in Danish). The project is car- ried out in the period August 2003 to August 2006 at the Traffic Research Group at Aalborg University in a co-operation with Ringkøbing and Viborg counties. In the project methods for identification, analysis and improvement of grey (hazardous) road sections are devel- oped. However, focus in this paper is only on the identification method developed.